SEROLOGICAL AND MOLECULAR EVALUATION OF MIGRATORY TRICHINELLA SPIRALIS LARVAE IN BLOOD OF HUMANS IN KADUNA METROPOLIS, NIGERIA - Ojodale, Paul Isaac; Inabo, Helen Ileigo; Ella, Elijah Ekah; Okubanjo, Oluyinka Oluseyi (FUDMA JOURNAL OF SCIENCES, 2021)
Trichinellosis is an important food-borne zoonotic disease with public health implications and a worldwide distribution. In this study, Polymerase Chain Reaction (PCR) procedure using species specific ATP6 primers was used to detect the presence of migratory Trichinella spiralis larval mitochondrial ATP6 synthase F0 subunit (ATP6) gene, after detection of antibodies to Trichinella excretory-secretory (E/S) antigen using Enzyme-linked Immunosorbent Assay (ELISA), in blood of humans in Kaduna metropolis, Nigeria. The sera of 210 participants were tested for antibodies to Trichinella E/S antigen. Overall seroprevalence rate of 39% (82/210) was recorded using ELISA. Out of the 9 ELISA samples selected randomly, PCR detected migratory Trichinella spiralis larval ATP6 gene in 4 (44.4%) at the amplicon size of 250 base pairs using the whole blood of the participants.  The 9 samples comprised 7 seropositive and 2 seronegative. The bands at lanes 1, 2, 3 and 4 were positive for ATP6 while lanes 5,6,7,8 and 9 were negative for ATP6.  Lanes 4 and 5 were ELISA negative for anti-Trichinella antibodies. One in 5 of the 128 ELISA negative samples was positive for ATP6 representing a 25.6% prevalence rate by extrapolation.  PCR using ATP6 gene as a genetic marker is valuable for the detection of T. spiralis migratory larvae in blood samples of humans and consequently the early diagnosis of trichinellosis in humans.